Understanding Cultural Adaptation of U.S. Hispanic Immigrant Couples and Their Shopping Orientation toward Fashion Products. (1st September 2021) - Toloza, Laura P.; Cho, Eunjoo; Terrell, Amanda
Abstract : The purpose of this study was to explore acculturation levels of Hispanic immigrant couples in the United States, their general attitudes related to shopping (i.e., shopping orientation), and a potential connection between acculturation levels and shopping orientation. Qualitative data were gathered by interviewing 15 Hispanic married couples who were born and raised in a Hispanic country and moved to the United States after the age of 18. Interviews were conducted in Spanish using snowball sampling. Findings revealed that Hispanic immigrants maintained their original culture while adopting the host culture. Most participants were oriented toward quality, price, brand, time, and recreational consciousness when shopping for fashion products. Whereas males were more inclined to be time‐conscious, females were more price‐ and recreational‐conscious. The findings suggest acculturation is closely linked to Hispanic shoppers' orientation. Thus, understanding acculturation levels among targeted ethnic shoppers is important to discover their general attitudes toward shopping for fashion products.